Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1111/jgs.15834
|View full text |Cite
|
Sign up to set email alerts
|

Inhaler Review in Older Adults with Asthma or COPD: A Cost‐Effectiveness Study and a Perspective in Portugal

Abstract: OBJECTIVES Older patients with asthma or chronic obstructive pulmonary disease are particularly susceptible to exacerbations that may be associated with incorrect use of inhalers. Educational programs with inhaler technique review seem to be effective, but no studies have addressed their cost‐effectiveness in older adult patients. The objective was to perform a cost‐effectiveness analysis of education programs in older patients and estimate the cost benefit of applying such a program in Portugal. DESIGN We dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 40 publications
(94 reference statements)
0
10
0
2
Order By: Relevance
“…In counselling, patients are always the expert when it comes to their own life, and counselling which takes into account the client's life situation will help achieve the treatment goals (Rajala et al 2018). The quality of asthma counselling has also been shown to reduce the cost of care (Haahtela et al 2017;Maricoto et al 2019) and amount of sick leave (Haahtela et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In counselling, patients are always the expert when it comes to their own life, and counselling which takes into account the client's life situation will help achieve the treatment goals (Rajala et al 2018). The quality of asthma counselling has also been shown to reduce the cost of care (Haahtela et al 2017;Maricoto et al 2019) and amount of sick leave (Haahtela et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some process indicators such as assessment on inhaler technique and drug adherence had not been included. This gap will need to be lled as evidence has revealed that inhaler technique education signi cantly reduced exacerbation rate (24), and is shown to be more cost-effective (25). Subsequent studies focusing on the long-term outcome criteria and inhaler technique may help provide a more comprehensive picture of COPD management.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some process indicators such as assessment on inhaler technique and drug adherence had not been included. This gap needs to be lled in future studies as evidence has shown that inhaler technique education signi cantly reduces the exacerbation rates (24) and is more cost-effective (25). Subsequent studies focusing on the long-term outcome criteria and inhaler technique may help provide a better guide for COPD assessment.…”
Section: Discussionmentioning
confidence: 99%